PENGARUH TEKANAN EKSTERNAL, AKUNTABILITAS, KETIDAKPASTIAN LINGKUNGAN DAN PENGENDALIAN INTERNAL TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN - Luh Budiartini; I Putu Deddy Samtika Putra (UNHI Press, 2021)
Financial transparency is is freedom to obtain information about aspects of financial performance in a comprehensive and open report manner which is summarized both positive and negative, accurate, timely, decisive and balanced through the media in the form of the presentation of financial statements that can be accessed by various interested parties with the assumption that the public has the right to know information. The purpose of this study is to provide the effect of external pressures, accountability, environmental uncertainty and internal control on the application of financial reporting transparency. Thise reasearch was conducted at OPD in Badung Regency. The population in this study were all apparatus work units totaling 8212 people. The sampling technique is using purposive sampling method, so that a sample of 114 people from 38 OPD is obtained. The analysis technique used is Multiple Regression Analysis. Test results show that external pressures and accountability had a positive and significant effect on the application of financial reporting transparency. While environmental uncertainty and internal control do not have significant effect on the application of financial reporting transparency.